Fibroadenoma of axillary supernumerary breast evaluation and treatment - Saini, Vikram; Kataria, Kamal; Yadav, Rajni; Rathore, Yashwant Singh (International Surgery Journal, 2023)
Supernumerary breast is a congenital anomaly of the breast and found in 2% to 6% of the general population. The most frequent site of a supernumerary breast is the axilla (60-70%). We are discussing a case with fibroadenoma in axillary supernumerary breast in a 40 year multiparous lady with history of fibroadenoma in opposite breast. There was diagnostic dilemma due to unusual presentation of common benign breast finding in supernumerary breast. Diagnosis of fibroadenoma confirmed with excision and tissue histopathology. Supernumerary breast tissue may undergo all pathologic changes that occur in normally positioned breasts. Fibroadenoma has been rarely described in supernumerary breast tissues. Any lump in axilla must be evaluated with suspicion as carcinoma arising in the ectopic breast tissue has poorer prognosis due to difficult evaluation, early lymph node involvement and more difficult surgical excision. Fibroadenoma of axillary supernumerary breast is rare condition but its evolution and excision in case for confirm diagnosis is necessary to rule out any malignancy.